Increasing Local Government E-Government Innovation in Achieve Good Government - Dewi Ervina Suryani; Juli Yanti Roslina Tindaon; Meyrisa br Tarigan; Can Harato Bawamenewi (Budapest International Research and Critics University, 2022)
This research is useful in explaining how: (1) to find out the obstacles faced by the Office of Women's Empowerment and Child Protection in handling street children in Medan City, (2) to explain the function of the Medan City Women's Empowerment and Child Protection Service when participating in the handling of children. Streets in Medan City. Normative and empirical methods are the methods that will be used. Normative research is defined in terms of methods of studying laws and regulations. Empirical legal research is included in the legal research method used to describe field conditions directly, using data collection techniques and interviews with North Sumatra PPPA officials, Medan City Social Service officials, street children, and Documentation Studies. Moreover, the data analysis used is tertiary data analysis which is analyzed descriptively, and quantitative data are presented descriptively. The results of this study can be concluded what the roles in handling street children carried out by the Office of Women's Empowerment and Child Protection in Medan City and the obstacles faced are.